Study about the sediment load and the bed load pattern at Galing River - Chan, Cheow Fah (2014)
Sediment is a naturally occurring particle that is broken down by the processes of weathering and erosion, which particles that with varying sizes that can be transported by fluid and flow along the fluid matter. The erosion or any other reason will cause the bed load increase at the river. It will make the river of the depth decrease. As the depth of the river decrease while the volume of the flow rate still same, it will cause the flooding when overflow. This study identified and analyzed about the bed load of this river and found out the sediment pattern from the sedimentation process. The purpose of the study was identified the size and types of sediment, analyzed the bed load discharge and identified the sediment pattern at Galing River. The study conducted at 3 stations, which are located at upstream, middle stream and downstream of the Galing River. The methods used to analyze sediment transport were Schoklitsch formula and Meyer-Peter Muller formula. In this-research, the-sizes-and-types of the-sediment at Galing River are determined, and the parameter of the grain size diameter need to conduct the sediment transport analysis had been found out. Meyer-Peter Muller and Schoklitsch showed there were less sediment discharge due to the low velocity and several criteria of tlie Galing River. In addition, the patterns of the bed load are variable in depth within the period of the research; it shows there was movement of particle along the Galing River.